2011
DOI: 10.1016/j.joca.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Change in knee osteoarthritis cartilage detected by delayed gadolinium enhanced magnetic resonance imaging following treatment with collagen hydrolysate: a pilot randomized controlled trial

Abstract: These preliminary results suggest that the dGEMRIC technique may be able to detect change in proteoglycan content in knee cartilage among individuals taking collagen hydrolysate after 24 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(126 citation statements)
references
References 18 publications
0
121
0
5
Order By: Relevance
“…In several clinical trials, the efficacy of oral collagen peptide supplementation could be demonstrated in osteoarthritic patients (McAlindon et al 2011;Benito-Ruiz et al 2009;Adam 1991;Krug 1979;Oberschelp 1985;Bruyère et al 2012). After treatment, significantly reduced pain and increased mobility were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several clinical trials, the efficacy of oral collagen peptide supplementation could be demonstrated in osteoarthritic patients (McAlindon et al 2011;Benito-Ruiz et al 2009;Adam 1991;Krug 1979;Oberschelp 1985;Bruyère et al 2012). After treatment, significantly reduced pain and increased mobility were reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical relevance of the observed effects needs to be clarified. In a placebo-controlled trial, McAlindon et al (2011) demonstrated increased content of proteoglycan as part of the ECM of cartilage tissue in patients with mild osteoarthritis after 10 g of collagen peptide intake. In addition, clinical studies with patients suffering from degenerative joint diseases showed an improvement in pain symptoms (Bello and Oesser 2006;Benito-Ruiz et al 2009;Bruyère et al 2012;Moskowitz 2000).…”
Section: Introductionmentioning
confidence: 99%
“…McAlindon and colleagues (31) showed that consuming 10 g collagen hydrolysate/d resulted in an increase in collagen within the knee. In agreement with this finding, a 24-wk randomized clinical trial in athletes showed that collagen hydrolysate significantly decreased knee pain (32).…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) scan has been increasingly used to confirm the diagnosis, define the stages and document the evolution of OCL [21,22]. The reliability of the method to recognize cartilage changes after collagen hydrolysate (Fortigel ® ) intake was demonstrated by McAlindon [23]. A single center, prospective, randomized, placebo-controlled, double blind trial included 30 patients with mild knee osteoarthritis, whose cartilage changes were followed by two MRI techniques (delayed gadolinium enhanced magnetic resonance imaging of cartilage -dGEMRIC or T2 mapping) before and after collagen hydrolysate nutritional supplementation.…”
Section: Discussionmentioning
confidence: 99%